Wages and Employment in a Random Social Network with Arbitrary Degree Distribution - IOANNIDES, Yannis M; Soetevent, Adriaan R (American Economic Review, 2006)
Wages and Employment in a Random Social Network with Arbitrary Degree Distribution by Yannis M. Ioannides and Adriaan R. Soetevent. Published in volume 96, issue 2, pages 270-274 of American Economic Review, May 2006